Addition of SHR-1701 to first-line capecitabine and oxaliplatin (XELOX) plus bevacizumab for unresectable metastatic colorectal cancer - Miao-Zhen Qiu; Yuxian Bai; Jufeng Wang; Kangsheng Gu; Mudan Yang; Yifu He; Cheng Yi; Yongdong Jin; Bo Liu; Feng Wang; Yu-kun Chen; Wei Dai; et al. (Signal Transduction and Targeted Therapy, 2024)
Abstract This phase 2/3 trial (NCT04856787) assessed the efficacy and safety of SHR-1701, a bifunctional protein targeting PD-L1 and TGF-β, in combination with BP102 (a bevacizumab biosimilar) and XELOX (capecitabine plus oxaliplatin) as a first-line treatment for unresectable metastatic colorectal cancer (mCRC). In this phase 2 study, a total of 62 patients with untreated, histologically confirmed colorectal adenocarcinoma and no prior systemic therapy for metastatic disease were enrolled. Patients received SHR-1701 (30 mg/kg), bevacizumab (7.5 mg/kg), and oxaliplatin (130 mg/m2) intravenously on day 1, along with oral capecitabine (1 g/m2 twice daily) on days 1–14 of 21-day cycles. Up to eight induction cycles were administered, followed by maintenance therapy for responders or those with stable disease. The primary endpoints were safety and objective response rate (ORR) per RECIST v1.1. The combination achieved an ORR of 59.7% and a disease control rate (DCR) of 83.9%. Median progression-free survival (PFS) was 10.3 months (95% CI: 8.3–13.7), with 6- and 12-month PFS rates of 77.2% and 41.3%, respectively. The estimated 12-month overall survival (OS) rate was 67.7%. Grade ≥3 treatment-related adverse events (TRAEs) were reported in 59.7% of patients, with anemia and neutropenia (8.1% each) being the most common. Retrospective DNA sequencing revealed that high tumor mutational burden, neo-antigens, and SBS15 enrichment correlated with better responses. Elevated baseline lactate dehydrogenase was linked to shorter PFS. SHR-1701 combined with XELOX and bevacizumab demonstrated a manageable safety profile and potent antitumor activity in unresectable mCRC.